Analisis Kepatuhan terhadap Antiretroviral dan Hubungannya dengan Kualitas Hidup Pasien HIV : Tinjauan Literatur - Panjaitan, Pretty Farida; Seftika Sari; Neni Frimayanti (LPPM, Universitas Muhammadiyah Riau, 2025)
Because it directly affects the level of viral suppression and the patient's quality of life, adherence to antiretroviral (ART) medication is an important component in HIV/AIDS treatment. According to many studies, high ART adherence is correlated with better physical, psychological, and social quality of life. Many factors can affect adherence, including therapy regimen, drug side effects, patient mental condition, and economic and social issues. This study was conducted based on six studies published in scientific journals to evaluate the relationship between HIV patients' quality of life and their adherence to antiretroviral drugs. This review used publications from the last ten years collected from the Publish or Perish and PubMed databases using the keywords adherence, antiretroviral, quality of life, and HIV. Articles that discussed the relationship between ART adherence and HIV patients' quality of life used quantitative or qualitative methods with valid measurement tools. The results showed that patients with an adherence rate of at least 90% had better viral suppression and better quality of life. The main factors that increased adherence were simpler ART regimens, milder side effects, support from health workers, and patient education. ART side effects, mental health problems (such as depression and anxiety), economic issues, and access are issues that hinder adherence